Meningkatkan Kemampuan Membaca Nyaring Kalimat Sederhana dengan Menggunakan Media Kartu Kata Siswa Kelas II SD - Wa Ode Riniati (CV. Ulil Albab Corp, 2022)
The low ability of students in reading at SD Negeri 2 Lakudo is the reason for this research. The purpose of this research study is to determine the improvement of reading aloud using word card media. This research is a Classroom Action Research. The research subjects were all second grade students of SD Negeri 2 Lakudo. Data analysis techniques were carried out through qualitative and quantitative methods. Classical student learning indicators have reached 75%. Based on the results of the study, it can be concluded that the use of word card learning media can improve reading skills. At the pre-cycle stage, the percentage of completeness of new students reached 31.25%, in the first cycle the percentage of completeness reached 56.75%, and in the second cycle the percentage of completeness reached 81.25%. Based on the learning outcomes and activities of teachers and students, it can be concluded that using word card learning media can improve the ability to read aloud simple sentences in Indonesian class II students of SD Negeri 2 Lakudo